Spatial-temporeral changes in the geomagnetic field and seismisity - Orlyuk, M.I.; Marchenko, A. V.; Romenets, А. A. (Geofizicheskiy Zhurnal, 2017)
This paper presents the results of an analysis of spatial-temporeral changes in the Earth’s magnetic field and its seismicity for the period 1950—2015. The International Geomagnetic Field of the 12 generation (BIGRF-12) was analyzed. This model allows one to study the characteristic features of magnetic anomalies with dimensions of the first thousands of kilometers. To determine the temporal changes in the geomagnetic field (dB/dt), digital datasets of BIGRF were developed for the period 1950—2015 in a 1°Ч1° grid and for an interval of 5 years. Temporal changes were divided into the virtual long-wave core-generated and short-wave mantle-lithospheric — generated components. There were revealed 2 negative and 3 positive foci of the core-generated component. For the 65 y period the component changes in these foci range from –6600 to 2000 nT (from –100 to 30 nT/y), the foci being characterized by the significant westward drift. 12 positive and 10 negative foci were delineated in the mantle-lithospheric-caused component. During 65 years most of the foci do not change their location. The changes in magnitude of positive and negative foci are 175—490 nT, (2,5—7,5 nT/y) and –(220—535) nT, (–(3,4—8,2) nT/y) respectively. In the southwestern domain of the Earth the intensity of seismicity is lower and the core-originated component is significantly decreased in comparison with the northwestern domain. The relationship is observed between areas of increased seismic activity, foci of the mantle-lithospheric component of the geomagnetic field and areas of its positive increase, which tectonically correspond to the junction zones of lithospheric plates of the «subduction», «collision» and «mid-ocean-rift» types. On the basis of the regularities revealed, two mechanisms of such an association are proposed: a) «temperature-magnetic», caused by discending the magnetic blocks of the oceanic crust in a subduction zone and also serpentinization of ultrabasic rocks of the upper mantle; b) «fluid-gas-magnetic», based on the formation and transformation of ferruginous minerals under the influence of the mantle gases and fluids. The magnetic blocks of the Earth’s lithosphere are more solid than those of the non-magnetic. Therefore, within the blocks, as well as on their margins, the accumulation of large stresses is possible and, consequеntly, the preconditions are created for the formation of earthquake foci.